2022
DOI: 10.1530/eje-21-1248
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for the prevention of adrenal crisis in adults with primary adrenal insufficiency: a systematic review

Abstract: Objective: The incidence of adrenal crisis remains high, particularly for people with primary adrenal insufficiency, despite the introduction of behavioural interventions. The present study aimed to identify and evaluate available evidence of interventions aiming to prevent adrenal crisis in primary adrenal insufficiency. Design: Systematic review of literature and theoretical mapping. Methods: MEDLINE, MEDLINE in Process, EMBASE, ERIC, Cochrane CENTRAL, CINAHL, PsycINFO, the Health Management Information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
(164 reference statements)
0
3
0
Order By: Relevance
“…Given the low prevalence of Addison's disease and the variability in patient experiences, it is possible to individualise daily steroid management of Addison's disease and education plans to prevent adrenal crises. Shepherd et al (2022) discussed the use of behaviour change theory to aid in self-management rather than relying on a purely educational model. This was identified in previous work where some individuals with Addison's disease continued to have adrenal crises despite being well educated (Shepherd et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Given the low prevalence of Addison's disease and the variability in patient experiences, it is possible to individualise daily steroid management of Addison's disease and education plans to prevent adrenal crises. Shepherd et al (2022) discussed the use of behaviour change theory to aid in self-management rather than relying on a purely educational model. This was identified in previous work where some individuals with Addison's disease continued to have adrenal crises despite being well educated (Shepherd et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, assessment of outcomes such as behaviour change, and frequency of adrenal crisis or hospitalisations was not reported. The authors concluded that there is a need to develop behaviour change interventions to support patients with AI to prevent adrenal crisis ( 32 ).…”
Section: Introduction: Self-management For Patients With Adrenal Insu...mentioning
confidence: 99%
“…The adrenal crisis incidence remains high, particularly for people with primary adrenal insufficiency, despite the behavioral intervention's introduction (Shepherd et al 2022). The adrenal insufficiency new presentation symptoms can range from nonspecific minor symptoms to a life-threatening adrenal crisis with hemodynamic instability (Ten et al 2001, Charmandari et al 2014.…”
Section: Introductionmentioning
confidence: 99%